2020
DOI: 10.3892/mmr.2020.11246
|View full text |Cite
|
Sign up to set email alerts
|

miR‑27a‑3p negatively regulates osteogenic differentiation of MC3T3‑E1 preosteoblasts by targeting osterix

Abstract: osteoporosis is a complex multifactorial disorder characterized by microarchitectural deterioration, low bone mass, and increased risk of fractures or broken bones. Balanced bone remodeling is tightly regulated by the differentiation, activity and apoptosis of bone-forming osteoblasts and bone-resorbing osteoclasts. Micrornas (mirs) are dysregulated in osteoporosis, but whether they control osteogenic differentiation and skeletal biology, or could serve as therapeutic targets remains to be elucidated. The pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 39 publications
1
20
0
Order By: Relevance
“…Serum levels of miR-27a-3p are elevated in pancreatic cancer, CRC, and PC, demonstrating its potential as a non-invasive biomarker [ 143 , 144 , 145 ]. miR-27a-3p is involved in bone metabolism and negatively regulates osteogenic differentiation [ 146 ]. It is part of the aforementioned 23a/27a/24-2 miRNA cluster, which is involved in both oncogenesis and osteoblast differentiation by targeting RUNX2 and SATB2 [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Serum levels of miR-27a-3p are elevated in pancreatic cancer, CRC, and PC, demonstrating its potential as a non-invasive biomarker [ 143 , 144 , 145 ]. miR-27a-3p is involved in bone metabolism and negatively regulates osteogenic differentiation [ 146 ]. It is part of the aforementioned 23a/27a/24-2 miRNA cluster, which is involved in both oncogenesis and osteoblast differentiation by targeting RUNX2 and SATB2 [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, microRNA-27a-3p was upregulated in the serum of patients with osteoporosis. Further experiments have proven that microRNA-27a-3p functionally represses the osteoblast differentiation by directly binding to OSX, which synergistically promotes osteogenesis and bone formation [107].…”
Section: Micrornas Involved In Osteogenesis Transcription Factorsmentioning
confidence: 99%
“…Comparison between osteoporotic patients and controls [ 16 , 20 , 22 , 24 , 27 , 29 , 31 , 32 , 34 , 35 , 36 , 40 , 41 , 44 , 45 , 47 , 50 , 51 , 52 , 53 , 55 , 59 , 61 , 63 ]…”
Section: Serum Mirnas As Clinical Potential Biomarkers For Human Ostementioning
confidence: 99%
“…MiR-27a-3p, miR-96, and miR-637 target osterix, inhibiting osteogenic differentiation [ 26 , 59 ]. The experiment of a mice model showed that repetitively agomiR-96-injected young mice had significantly decreased BMD compared with vehicle-treated mice, and aged mice treated with antagomir-96 had higher bone strength compared to controls [ 26 ].…”
Section: Mechanisms Of the Identified Mirnasmentioning
confidence: 99%
See 1 more Smart Citation